232-IENDOAORTIC BALLOON CLAMPING AND TRANSTHORACIC AORTIC CLAMPING ARE BOTH SAFE AND EFFECTIVE IN MINIMALLY INVASIVE MITRAL VALVE SURGERY. (October 2014) - Rinaldi, M.; Krakor, R.; Bentala, M.; Casselman, F.; Candolfi, P.; Barbero, C.; Goldstein, J.
Abstract : Objectives: Minimally invasive mitral valve surgery (MIMVS) has become a widespread procedure in recent years. Mode of perfusion and aortic clamping are still debated questions. The aim of this study is to compare the results between transthoracic aortic clamping (TTC) and endoaortic balloon clamping (EAC) in a multicentric, retrospective study. Methods: Data from 3 experienced centres in both TTC and EAC were prospectively collected and retrospectively analysed. Five hundred consecutive patients undergoing MIMVS ± tricuspid valve and/or atrial fibrillation surgery received either TTC ( n = 250) or EAC ( n = 250). Age, gender, logistic Euroscore, ejection fraction, associated surgery and mitral repair rate were similar. A higher incidence of previous cardiac operations was observed in the EAC group (TTC 8.8% vs EAC 16.8%, P = 0.007). Results: X-clamp and extracorporeal circulation time were similar (TTC 77.3 ± 26.5 min vs EAC 74.4 ± 29.3 min, and TTC 115.2 ± 35.0 min vs EAC 111.9 ± 38.6 min, respectively). Thirty-day mortality was similar (1.6% vs 0.8%). Stroke rate was 0.8% in both groups. Reoperation for bleeding and blood transfusion were higher in the TTC group (TTC 11.2% vs EAC 3.2%, P < 0.001 and TTC 4.2 ± 4.4 vs EAC 3.0 ± 2.4 units, P = 0.019, respectively). No difference was found in respiratory failure, renal failure, and major vascular complications. Conclusion: Despite recent concerns arising about EAC, this large multicentre study shows equivalence in term of safety and effectiveness of this technique compared with TTC. Reduction in postoperative bleeding was observed in the EAC group despite the higher rate of complex redo cases.